Evaluasi Kebijakan Masa Studi di Perguruan Tinggi (Studi di Fakultas Ilmu Administrasi Universitas Brawijaya) - Jaedi, Jaedi; Supriyono, Bambang; Muluk, M. R. Khairul (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2019)
This study aims to describe the criteria of the successful study period in higher education and its impact on study period policy. The study adopted a descriptive qualitative research design. Data were collected through observation, interviews, and documentation in six study programs on the Faculty of Administrative Sciences Universitas Brawijaya. Interactive analysis model by Miles, Huberman & Saldana (2014) which consist of data collection, data display, data condensation, and verifying or conclusion drawing was utilized to analyze and present findings. The results showed that study period policy in the Faculty of Administrative Sciences Universitas Brawijaya has been carried out well and successfully. It can be seen from the existence of the main tasks and functions that are inherent in the organizational structure and the various real efforts that supported the policies that positively impacted in the student’s study period.